Analisis Struktur Ukuran dan Tingkat Kematangan Gonad Ikan Tembang (Sardinella fimbriata) Sebagai Indikator Pemanfaatan Sumberdaya di Perairan Kwandang - Rosyikhul F.S M Nango; Dewi Shinta Achmad; Tusaban Tusaban; Nur Jihan Fareranty Piu (Pusat Riset dan Inovasi Nasional, 2026)
Small pelagic fisheries play an important role in food security, coastal livelihoods, and local fishery economies in Indonesia. Sardinella fimbriata is one of the economically important small pelagic fish species widely utilized in coastal communities. However, increasing fishing pressure may alter population size structure and reduce reproductive sustainability. This study aimed to analyze the size structure, gonad maturity stage, and exploitation status of Sardinella fimbriata in Kwandang Waters, Tomini Bay, Indonesia. The research was conducted from August to November 2025 using a descriptive quantitative approach. A total of 1,560 fish samples collected from commercial landings were measured for total length and examined macroscopically for gonad maturity. Data were analyzed using length-frequency distribution, maturity proportion, and logistic regression to estimate length at first maturity (L₅₀). The results showed that fish length ranged from 8.0 to 19.9 cm and was dominated by the 12.0–15.9 cm size group, accounting for 75.45% of total samples. Immature gonads dominated the catch, representing 91.35% of individuals, while mature fish accounted for only 8.65%. Logistic regression estimated L₅₀ at 16.72 cm, whereas the average catch length was 13.56 cm with an Lc/L₅₀ ratio of 0.81. These findings indicate that most fish were captured before reaching reproductive maturity, suggesting growth overfishing conditions. The study highlights the importance of minimum catch size regulation, selective fishing gear, and routine biological monitoring to support sustainable management of small pelagic fisheries in Tomini Bay.